2004
DOI: 10.1140/epje/i2004-10064-6
|View full text |Cite
|
Sign up to set email alerts
|

Transient-state method for coupled evaluation of Soret and Fick coefficients, and related tortuosity factors, using free and porous packed thermodiffusion cells: Application to CuSO4 aqueous solution ( 0.25M)

Abstract: The measurement of Soret coefficients in liquids is not easy and usually not very precise because the resulting concentration gradient is small and moreover can be perturbed by undesired convection currents. In order to suppress, or to drastically reduce these convection currents, the use of a porous medium is sometimes suggested. The question arises as to whether the Soret coefficient is the same in free fluid and in porous medium. This is the aim of this paper. To this end, for a given liquid mixture, the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 7 publications
2
23
0
Order By: Relevance
“…The thermal permeability δ T is thus of the same order of magnitude as δ p , but negative, indicating thermal diffusion transpiring from low to high temperatures. [23] corroborates that the thermal diffusion factor α remains valid when considering porous materials, so such ratio's are equally valid for vapour diffusion in porous materials.…”
Section: Thermodynamic Elaborationsupporting
confidence: 72%
“…The thermal permeability δ T is thus of the same order of magnitude as δ p , but negative, indicating thermal diffusion transpiring from low to high temperatures. [23] corroborates that the thermal diffusion factor α remains valid when considering porous materials, so such ratio's are equally valid for vapour diffusion in porous materials.…”
Section: Thermodynamic Elaborationsupporting
confidence: 72%
“…al. [32], and Mialdun and Shevtsova [17] The analysis shown here is based on measuring the composition and temperature as function of distance from the heat source for fixed time. In an experimental setup, it may be more convenient to measure the composition as function of time for a fixed distance from the heat source.…”
Section: Discussionmentioning
confidence: 99%
“…inaccuracies in measuring the porosity and other thermophysical parameters). The authors who have conducted experimental studies of species separation in vertical thermogravitational columns [19,20] reported errors of the same order of magnitude. …”
Section: Methodsmentioning
confidence: 97%
“…The first experiment was with (Cell 1 ) using an aqueous solution of CuSO 4 whose concentration expressed as mass fraction was 0.0733. This solution has been studied previously [18,19]. For the presented experiment, we chose an inclination of 75°from the vertical with the cold wall at 10°C and the hot wall at 30°C (Le = 130 ± 8, Ra = 1.500 ± 0.075 and w = 0.40 ± 0.05).…”
Section: Methodsmentioning
confidence: 99%